STATUS DAN PERAN BADAN PERMUSYAWARATAN DESA (BPD) DI DESA BARAN MELINTANG KECAMATAN PULAU MERBAU KABUPATEN KEPULAUAN MERANTI - Said Ridho Amal; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in the village of Baran Melintang KecamatanPulau Merbau Kabupaten Kepulauan Meranti in order to obtain information aboutthe role of the Implementation of the Village Consultative Body. Problems in thisstudy were (1) A BPD role as a partner in the Village Head support the success ofdevelopment in 2014 ago in the village of Baran Melintang Kecamatan PulauMerbau Kabupaten Kepulauan Meranti? (2) What factors influence theimplementation of the BPD's role in carrying out its function as a partner in theVillage barrage of Village Baran Melintang Kecamatan Pulau Merbau KabupatenKepulauan Meranti. The title of this research is